Interaction Between Two Jackiw-Rebbi States in Interfaced Binary Waveguide Arrays with Cubic-quintic Nonlinearity - Tran, Xuan Truong; Nguyen, Nhu Xuan; Nguyen, The Quang; Nguyen, Van Toan; Nguyen, Tuan Linh (Communications in Physics, 2021)
We study the coupling and switching effects of two discrete relativistic quantum Jackiw-Rebbi states in interfaced binary waveguide arrays with cubic-quintic nonlinearity. Like in the case with Kerr nonlinearity, two Jackiw-Rebbi states can couple efficiently to each other in the low-power regime, show the switching effect in the intermediate-power regime, and possess the trapping effect in the high-power regime. However, in the case with cubic-quintic nonlinearity, if the input Jackiw-Rebbi state power is increased further, one can observe the quasi-linear coupling effect between two Jackiw-Rebbi states which has not been found between two Jackiw-Rebbi states in interfaced binary waveguide arrays with Kerr nonlinearity